2021
DOI: 10.1515/opag-2021-0219
|View full text |Cite
|
Sign up to set email alerts
|

Storage root yield and sweetness level selection for new honey sweet potato (Ipomoea batatas [L.] Lam)

Abstract: Multilocation experiments are the steps to determine the genotype stability being tested. Honey sweet potato is a superior agricultural product from West Java, Indonesia. High yield and sweetness are the important traits of the new honey sweet potato breeding lines. In this study, the sweetness level used was the soluble solid level (°brix). The goals of this study were to determine the effects of genotype by environment interactions (GEIs) and to select for storage root yield stability and sweetness among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…have the same power in estimating genotype stability; therefore, the three stability parameters were suggested to select stable genotypes [9,18]. Based on the average ranks (AR), the maize hybrid of MH2 followed by MH8, MH9, and MH5 had a small AR value; therefore, these maize hybrids can be proposed as the most stable genotype.…”
Section: Evaluation Of High Yielding Maize Hybrids Usingmentioning
confidence: 99%
See 2 more Smart Citations
“…have the same power in estimating genotype stability; therefore, the three stability parameters were suggested to select stable genotypes [9,18]. Based on the average ranks (AR), the maize hybrid of MH2 followed by MH8, MH9, and MH5 had a small AR value; therefore, these maize hybrids can be proposed as the most stable genotype.…”
Section: Evaluation Of High Yielding Maize Hybrids Usingmentioning
confidence: 99%
“…In some cases, maize yields are strongly influenced by GEIs due to environmental changes [5][6][7][8]. Studies also reported that GEIs complicate the selection process for crops like sweet potato in Indonesia [9], durum wheat in Turkey [10], yellow passion fruit in Brazil [11], and cotton in China [12]. Therefore, GEI analysis is important in evaluating superior genotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection is an important stage in plant breeding programs in determining superior genotypes. Several researchers have selected several characters including Yan and Frégeau-reid (2018) on oat yield, agronomic and quality traits, and Karuniawan et al (2021) on the yield and sweetness traits of sweet potatoes. Selection on multiple traits allows researchers and farmers to select genotypes that excel at multiple traits.…”
Section: Introductionmentioning
confidence: 99%
“…Sweet potato farming, cassava, corn, and various bean types are the livelihoods of strategic residents in Madagascar, and most of the island's population consists of smallholders and herders, ranchers and farmers [2]. Tuber plants that play an important role in Indonesia include sweet potatoes [3]. One of the root crops in many countries is sweet potatoes [4].…”
Section: Introductionmentioning
confidence: 99%